(untitled) (The Pakistan Development Review, 2001)
Ensuring the survival and well being of children is a concern of families, communities, and nations throughout the world. Since the turn of the 20th century infant and child mortality in more developed countries has steadily declined and, currently, has been reduced to almost minimal levels. In contrast, although infant and child mortality has declined in the past three decades in most less developed countries, the pace of change and the magnitude of improvement vary considerably from one country to another. Children are at risk of both mortality and morbidity. The problem of malnutrition is widespread in developing countries and particularly severe in South Asian countries, where almost fifty percent of the undernourished children of the world live [Carlson and Wardlaw (1990)]. Rural populations are especially prone to malnutrition because they are more likely to be poor [Tinger (1998)]. The analysis of Demographic and Health Surveys (DHS) in 19 developing countries shows that children living in rural areas are more likely to be malnourished [Sommerfelt and Stewart (1994)].